2013
DOI: 10.1089/ten.tea.2012.0250
|View full text |Cite
|
Sign up to set email alerts
|

Production and Assessment of Decellularized Pig and Human Lung Scaffolds

Abstract: The authors have previously shown that acellular (AC) trachea-lung scaffolds can (1) be produced from natural rat lungs, (2) retain critical components of the extracellular matrix (ECM) such as collagen-1 and elastin, and (3) be used to produce lung tissue after recellularization with murine embryonic stem cells. The aim of this study was to produce large (porcine or human) AC lung scaffolds to determine the feasibility of producing scaffolds with potential clinical applicability. We report here the first atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 37 publications
2
151
0
Order By: Relevance
“…Lamin A/C appears to be efficiently depleted during the decellularization process, despite known challenges of completely removing nuclear matrix. In contrast, h H2A, appears enriched postdecellularization, despite reports of efficient DNA depletion (5,44,45). Similarly, cellular proteins such as cytoskeletal actins, tubulins, and mitochondrial ATP synthase subunit alpha-1 appear to be inefficiently removed by the decellularization process according to the peptide spectral match comparisons in Table I.…”
Section: Resultsmentioning
confidence: 97%
“…Lamin A/C appears to be efficiently depleted during the decellularization process, despite known challenges of completely removing nuclear matrix. In contrast, h H2A, appears enriched postdecellularization, despite reports of efficient DNA depletion (5,44,45). Similarly, cellular proteins such as cytoskeletal actins, tubulins, and mitochondrial ATP synthase subunit alpha-1 appear to be inefficiently removed by the decellularization process according to the peptide spectral match comparisons in Table I.…”
Section: Resultsmentioning
confidence: 97%
“…There is now considerable evidence that MSCs play a role in regeneration and repair (61,62,81,91,112,201) and in secretion of growth factors, immune modulators, and other factors that support the idea that MSCs may be better taken up in organ scaffolds (158,198,220), especially if scaffolds enhance their differentiation (86,219), presumably through cell-matrix interactions (64,161,174,232). Several studies have shown that MSCs can attach and proliferate in lung scaffolds (39,117,131,137). For example, MSCs derived from human adipose tissue and bone marrow on decellularized rat lungs express markers of pulmonary epithelial cells (117), although the source of the MSCs may play a role in their local behavior such as cell attachment, migration, and proliferation.…”
Section: Recellularization In Lung Bioengineeringmentioning
confidence: 99%
“…An important consideration (as with allogeneic transplants) is the immunological response of the transplant recipient to the bioengineered lung (102,131,189,190). Regardless of the materials used to engineer a lung, generalized immunosuppression will likely be the initial approach to minimizing rejection, although techniques to enhance acceptance of a bioengineered lung containing specific types of scaffold materials and cell types are obviously a major research focus [e.g., biocompatible materials, novel (ideally personalized) sources for stem cells, and cell differentiation techniques].…”
Section: Issues In Lung Bioengineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, parallel investigations have been conducted with murine (168,169), primate (170), and more recently human tissue (171)(172)(173), as well as analysis with different stem cell populations such as bone marrow-derived MSCs (174). This emergent field could have great implications for transplant medicine, where the possibility of using acellular cadaveric donor tissue could reduce numbers of patients waiting to receive a transplant from viable sources (175).…”
Section: Decellularised (Dc) Tissuementioning
confidence: 99%